2004
DOI: 10.1136/ard.2003.007245
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathic haemolytic anaemia and antiphospholipid antibodies

Abstract: Objective: To analyse the clinical and laboratory features of patients with thrombotic microangiopathic haemolytic anaemia (TMHA) associated with antiphospholipid antibodies (aPL). Methods: A computer assisted (PubMed) search of the literature was performed to identify all cases of TMHA associated with aPL from 1983 to December 2002. Results: 46 patients (36 female) with a mean (SD) age at presentation of TMHA of 34 (15) years were reviewed. Twenty eight (61%) patients had primary antiphospholipid syndrome (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 63 publications
0
80
0
3
Order By: Relevance
“…In one series of 56 patients with malignant hypertension, microangiopathic hemolytic anemia was present in 23 patients (8). Espinosa et al (9) reported that 13% of patients with systemic TMA showed malignant hypertension. On the other hand, the frequency of intrarenal TMA with malignant hypertension has not been well described (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…In one series of 56 patients with malignant hypertension, microangiopathic hemolytic anemia was present in 23 patients (8). Espinosa et al (9) reported that 13% of patients with systemic TMA showed malignant hypertension. On the other hand, the frequency of intrarenal TMA with malignant hypertension has not been well described (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have noted the relationship between TMA and the presence of antiphospholipid antibodies [151] . HUS and, less commonly, TTP and HELLP syndrome, may be the presenting manifestation [152] . The existence of TMA in association with APS forces to rule out the catastrophic variant of the syndrome.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…However, the efficacy of PE has been shown in other thrombotic microangiopathy and since CAPS is a critical situation with a high rate of mortality, it is recommended as part of the CAPS treatment [15].…”
Section: Diagnosismentioning
confidence: 99%